The effects of dilation with different sizes on post-endoscopic retrograde cholangiopancreatography pancreatitis after small biliary sphincterotomy - Meng, Wenbo; Mu, Peilei; Li, Xun (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Meng W, Yue P, Li X. The effects of dilation with different sizes on post-endoscopic retrograde cholangiopancreatography pancreatitis after small biliary sphincterotomy. Turk J Gastroenterol 2020; 31(10): 729-30.